Applications of crushing and grinding-based treatments for typical metal-containing solid wastes: Detoxification and resource recovery potentials. (1st December 2022) - He, Hongping; Yang, Bo; Wu, Deli; Gao, Xiaofeng; Fei, Xunchang
Abstract: Metal-containing solid wastes can induce serious environmental pollution if managed improperly, but contain considerable resources. The detoxification and resource recoveries of these wastes are of both environmental and economic significances, being indispensable for circular economy. In the past decades, attempts have been made worldwide to treat these wastes. Crushing and grinding-based treatments have been increasingly applied, the operating apparatus and parameters of which depend on the waste type and treatment purpose. Based on the relevant studies, the applications of crushing and grinding on four major types of solid wastes, namely spent lithium-ion batteries (LIBs) cathode, waste printed circuit boards (WPCBs), incineration bottom ash (IBA), and incineration fly ash (IFA) are here systematically reviewed. These types of solid wastes are generated in increasing amounts, and have the potentials to release various organic and inorganic pollutants. Despite of the widely different texture, composition, and other physicochemical properties of the solid wastes, crushing and grinding have been demonstrated to be universally applicable. For each of the four wastes, the technical route that involving crushing and grinding is described with the advantages highlighted. The crushing and grinding serve either mainstream or auxiliary role in the processing of the solid wastes. This review summarizes and highlights the developments and future directions of crushing and grinding-based treatments. Graphical abstract: Image 1 Highlights: Applications of crushing/grinding in typical solid wastes are reviewed These solid wastes differ in texture, composition, and physicochemical property Crushing/grinding be auxiliary or dominant in solid waste treatment Advantage of relevant technical routes and future direction are highlighted